Global Analysis the Potential Medicinal Substances of Shuangxia Decoction and the Process In Vivo via Mass Spectrometry Technology - Zhang, Chenning; Liu, Chuanxin; Wu, Hao; Wang, Jiaqi; Sun, Yu; Liu, Runhua; Li, Tianyi; Yu, Xue; Geng, Di; Sun, Yi-Kun (Frontiers in Pharmacology, 2021)
Shuangxia decoction is an effective traditional Chinese medicine formula for treating insomnia. Up to now, there has not been any report about the effective substances. An omics data processing method based on mass spectrometry technology is used to explore the chemical composition changes of shuangxia decoction, the components absorbed into the blood and brain, and to explore the anti-insomnia mechanism based on molecular docking technology. 49 chemical components in shuangxia decoction have been identified, and 51 new components generated by co-decoction have been discovered. It was found that 7404 compounds of shuangxia decoction were absorbed into the blood. 40 kinds of known compounds were quickly identified. and 15 new compounds generated by co-decoction were also found to be absorbed into the blood. By using UPLC-MS/MS method, it was confirmed that 10 compounds were absorbed into the blood and 9 compounds were absorbed into the brain, Furthermore, it is found that rosmarinic acid is mainly distributed in the hypothalamus and striatum, and caffeic acid is mainly distributed in the hypothalamus, striatum and hippocampus. Molecular docking results showed rosmarinic acid, danshensu and HMLA with GABAA receptor have excellent binding characteristics, even surpassing the pro-ligand. Danshensu and HMLA with dopamine D2 receptor also showed good binding energy. Our findings will help to further confirm the mechanism of shuangxia decoction for relieving insomnia, and we also establish a novel data processing method for supplementing the mechanism of the efficacy of other traditional Chinese medicine formula.